The Renaissance of a Food-Based Economy in Skowhegan - Lambke, Amber (Maine Policy Review, 2011)
This case study discusses the example of Skowhegan, Maine, which is seeing the rebirth of a local food-based economy, focused on the development of a local grist mill and farmer’s market
Keywords: Maine; food hub; local foods